The influence of case manager to patient satisfaction and service quality - Wangi, Puga Sharaz; Sundari, Sri (Universitas Aisyah Pringsewu, 2023)
Patient-Centered Care (PCC) in hospital service is crucial. Case management, administered by a case manager (CM), is one of PCC implementation. CM's objectives are to attain patient satisfaction and provide quality service. However, the concept of CM is still novel in Indonesia, especially among inpatients. The effect of the CM role on patient satisfaction and service quality remains to be determined. This study aims to measure and analyze the influence of CM on patient satisfaction and service quality. We used quantitative method with a cross-sectional approach. Questionnaires adapted from Korean-PSCCM, Case Management Quality Questionnaire (CMQQ), and adapted SERVQUAL were used to measure inpatient satisfaction and service quality. Data were analyzed with bivariate statistical analysis using SPSS. Data collecting was done between 1-30 March 2023, with total 42 respondents. The influences of CM to patient satisfaction and service quality were not statistically significant. (p = 0,973 ; and p = 0,944). In this study, the function of CM in patient care is not optimal in increasing patient satisfaction and service quality, as CM continues to work multiple shifts in other units and has limitations in addressing patient problems. Considering the increasing complexity of hospital services, future interventions are necessary to optimize clinical management (CM) function further. Abstrak: Pelayanan berfokus-pada pasien di rumah sakit merupakan hal yang penting. Salah satu implementasi dari hal tersebut adalah manajemen pelayanan pasien oleh MPP, yang bertujuan untuk mencapai kepuasan pasien dan memberikan pelayanan yang berkualitas. Namun, konsep MPP sendiri masih tergolong baru di Indonesia khususnya pada pasien rawat inap. Pengaruh peran MPP terhadap kepuasan pasien dan kualitas pelayanan masih harus dilakukan penelitian. Tujuan penelitian adalah untuk mengukur dan menganalisis pengaruh peran MPP terhadap kepuasan pasien dan kualitas pelayanan. Penelitian ini metode kuantitatif dengan pendekatan potong lintang. Kuesioner yang diadaptasi dari Korean-PSCCM, Case Management Quality Questionnaire (CMQQ), dan SERVQUAL yang diadaptasi untuk mengukur kepuasan rawat inap dan kualitas pelayanan. Data dianalisis dengan statistik bivariat menggunakan SPSS. Pengumpulan data dilakukan pada tanggal 1-30 Maret 2023 dengan jumlah responden sebanyak 42 orang. Pengaruh MPP terhadap kepuasan pasien dan kualitas pelayanan secara statistik tidak signifikan. (p = 0,973; dan p = 0,944). MPP tidak berpengaruh secara signifikan terhadap kepuasan rawat inap dan kualitas pelayanan. Namun, fungsi MPP tetap diperlukan karena kepuasan pasien dapat berfluktuasi dari waktu ke waktu; oleh karena itu, perlu untuk terus memantau aspek-aspek yang diidentifikasi saat ini tidak relevan dengan kepuasan pasien dan evaluasi kualitas layanan.